Analysing the Sustainability of Solid Waste Management from the Perspective of Adequate Legislation - Haidy Henry Dusim; Mohammad Tahir Mapa (2008)
This paper aims to analyse the sustainability of solid waste management from the perspective of policy. The previous studies have mainly focused on analysing the sustainability of solid waste management from the perspective of technology, however, little studies have focused on analysing the sustainability of solid waste management from the perspective of policy. In the context of this study, policy refers to adequate legislation. To conduct this study, Kota Kinabalu, Sabah is selected as a case study. Data are mainly collected from interviews, questionnaires and secondary data. Data collected from the interviews and secondary data are analysed through thematic analysis. Meanwhile, data collected from the questionnaires are analysed using the Statistical Package for the Social Sciences (SPSS). Based on the overall findings, the study found that the existing solid waste management in Kota Kinabalu still lack of adequate legislation, as it still lacks the element of the comprehensive legislation and specific legislation. Through conducting this study, it may help to shift the focus of analysing the sustainability of solid waste management purely from the perspective of technology to the perspective of policy. Besides, it may help to improve the sustainability of solid waste management system particularly from the perspective of policy.